Application of City Surveillance Systems with Technology Management in Abu Dhabi United Arab Emirates - Ali H. AL NEYADI; Abdul Jalil OMAR (Communications of International Proceedings, 2021)
Today closed-circuit television (CCTV) is widely used by law enforcement officials to detect and control crime senses in public places. This has led to a rather intensive debate about CCTV cameras and surveillance strategies concerning community effectiveness. This study analyses the importance of surveillance system and understanding the need of technology in the safety and security aspect in United Arab Emirates (UAE). Applying CCTV deals with three problem areas; lack of security solution, absence of IT security education and knowledge; and stakeholders’ contribution to public safety. This study proposes a smart City Surveillance model for monitoring not only the largest and main emirates in the U.A.E but the country as a whole. The result shows there is a high correlation between the independent variables (Authority control and monitoring, Government CCTV standards, and CCTV integrators) and the dependent variable (CCTV effectiveness). A careful throughout look and deep analysis for those surveillance systems within cities in UAE are critically analyzed. To answer research questions, a quantitative method is applied and a survey is conducted in the city of Abu Dhabi. The results of the study indicate that the system is a great help and is important in securing safety in public places and helps prevent criminal acts. The result of the study also shows that Authority has an important role in the implementation of the CCTV system in the emirate of Abu Dhabi.
Keywords: Authority control and Monitoring; Government CCTV Standards; CCTV Integrators; CCTV Effectiveness.